Simulations of Post-impact Skin/core Debond Growth in Sandwich Plates Under Impulsive Loading - Burlayenko, Vyacheslav N.; Sadowski, Tomasz (Journal of Applied Nonlinear Dynamics, 2026)
In this study, the transient dynamics of a sandwich plate with post impact zone is examined. The dynamic response of the sandwich plate is simulated by using the finite element code ABAQUS. The damage mechanics approach implemented into ABAQUS via cohesive elements is applied to model the debonding propagation under impulsive loading. To demonstrate the effectiveness of the FE model developed, a foam-cored sandwich plate with an initial penny-shaped impacted region is modelled. The influence of the skin-to-core debond on the global nonlinear dynamics of the sandwich plate is studied in detail.